An introduction to fuzzy systems - Dubois, Didier; Prade, Henri (Zielona Góra: Uniwersytet Zielonogórski)
This short paper introduces the notion of fuzzy sets as a tool for modelling sets with ill-defined boundaries. Fuzzy sets naturally appear when describing the meaning of natural language words pertaining to quantitative scales, or when modelling the notion of typicality. Three main semantics for fuzzy sets are respectively recalled: similarity, preference and uncertainty.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka